The Fragmentation of Knowledge in Physical Education [la Fragmentación del Conocer en Educación Física] - Toro-Arevalo, S (Federacion Espanola de Docentes de Educacion Fisica, 2021)
The study aimed at diagnosing the conceptual formation in physical education in Chilean high school students. The study used a descriptive cross-sectional methodology. A total of 659 students participated, 54% boys and 46% girls, aged between 13 and 14 years old, from the three educational units in the country; public schools (36.4%), subsidized schools (37.8%) and private schools (25.8%). A stratified probabilistic sampling was performed based on students’ educational dependence and gender. For the data collection, a questionnaire designed and validated with students of the Chilean curriculum was applied. The main results indicate that there are statistically significant differences between educational units, with specific results from Anova of f = 48,584 p <.05 in favor of private schools. In conclusion, the study shows a low disciplinary domain of the students in the different educational units, highlighting once more the need to seek innovative methodologies within this discipline in order to improve the learning of its conceptual dimension. © Copyright: Federación Española de Asociaciones de Docentes de Educación Física (FEADEF).